Oral hygiene in schools of 6 years of age of the Baños Rural Parish - Ecuador - Lucero Ulloa, Santiago (2020)
Objective To determine the degree of oral hygiene in 6-year-old schoolchildren in the rural parish of Baños. Materials and Methods The study had a descriptive quantitative approach. Use the data from the digital collection in the Epi INFO program. The sample consisted of 198 6-year-old schoolchildren, of which 94 are female students representing 47% of the sample and 104 male schoolchildren representing 53% of the sample. Results The results obtained showed that the children of the parish Baths indicated 64% in a Simplified Oral Hygiene Index equal to 0.9, a bacterial plaque index equal to 0.8 and the calculation index of 0.1. The educational centers of the parish six of them visualize a "good" oral hygiene and 3 manifestations a "regular" oral hygiene. Conclusions The  6-year-old schoolchildren of the Baños parish have good oral hygiene, with no difference between the two genders.